Ketogenic diet in treatment of Pediatric Refractory Epilepsy - Efficacy and potential Adverse Effects, A Review - Kaczmarek, Weronika; Szeląg, Karolina; Damian, Jan; Brzeźniak, Mikołaj; Fitz, Emilia; Mokracka, Julia; Gil, Kacper; Daniek, Justyna; Drelich, Krzystof; Karbowniczek, Aleksander; Kręcina, Filip; Grabarczyk, Alicja (Quality in Sport, 2026)
Background. Epilepsy affects 0,5-1% of children. It is more frequently resistant to anti-seizure drugs compared to the adult population. Ketogenic diet is a high-fat, low-carbohydrate nutrition style that has been widely used and researched as treatment for refractory pediatric epilepsy, giving a relatively safe alternative to more hazardous and invasive forms of seizure therapy. Aim. Discussion of efficacy and potential adverse effects of the ketogenic diet in treatment of pediatric refractory epilepsy, with additional overview of different ketogenic diet forms. Material and methods. A narrative review of the PubMed database using the following keywords was performed: ketogenic diet, KD, pediatric epilepsy, pediatric refractory epilepsy. The findings were analysed in terms of relevance, studied population and researched outcomes. Studies from the year 2015 or older were excluded. Results. Ketogenic diet was identified as highly effective in pediatric refractory epilepsy. Examined research shows a significant seizure frequency reduction in studied populations. Comparison between the classic ketogenic diet and its alternatives is inconsistent, but the efficacy seems to be comparable. The diet is reported to have frequent side effects, most commonly gastrointestinal, however they are usually mild and easy to prevent or treat. Conclusions. Ketogenic diet seems to be a relatively low-risk, effective option for treatment of refractory pediatric epilepsy. Possible adverse effects in majority should not be a reason for withdrawal.